DSM-5 cannabis withdrawal syndrome: Demographic and clinical correlates in U.S. adults. (1st February 2019) - Livne, Ofir; Shmulewitz, Dvora; Lev-Ran, Shaul; Hasin, Deborah S.
Highlights: Cannabis withdrawal syndrome is a highly comorbid, disabling condition. Cannabis withdrawal is associated with mood, anxiety, and personality disorders. Cannabis use disorders are strongly correlated with cannabis withdrawal syndrome. Anxiety and hostility are the most common symptoms of cannabis withdrawal syndrome. Abstract: Background: Cannabis withdrawal syndrome (CWS) was newly added to the Diagnostic and Statistical Manual of Mental Disorders in its most recent edition, DSM-5. With cannabis use increasing among U.S. adults, information is needed about the prevalence and correlates of DSM-5 CWS in the general population. This study presents nationally representative findings on the prevalence, sociodemographic and clinical correlates of DSM-5 CWS among U.S. adults. Method: Participants ≥18 years were interviewed in the National Epidemiologic Survey on Alcohol and Related Conditions-III (NESARC-III) in 2012-2013. Among the sub-sample of frequent cannabis users in the prior 12 months (≥3 times a week; N = 1527), the prevalence and demographic and clinical correlates of DSM-5 CWS were examined. Results: In frequent cannabis users, the prevalence of CWS was 12.1%. The most common withdrawal symptoms among those with CWS were nervousness/anxiety (76.3%), hostility (71.9%), sleep difficulty (68.2%) and depressed mood (58.9%). CWS was associated with significant disability (p < 0.001), and with mood disorders (adjusted odds ratios [aOR] = 1.9–2.6), anxiety disorders (aOR = 2.4–2.5), personality disorders (aOR = 1.7–2.2) and family history of depression (aOR = 2.5) but not personal history of other substance use disorders or family history of substance use problems. Conclusions: CWS is highly comorbid and disabling. Its shared symptoms with depressive and anxiety disorders call for clinician awareness of CWS and the factors associated with it to promote more effective treatment among frequent cannabis users.